2022
DOI: 10.17219/acem/150032
|View full text |Cite
|
Sign up to set email alerts
|

The functional and radiographic outcomes following distal radius fracture treatment in a cast for 4 and 6 weeks in the elderly: A randomized trial

Abstract: Background. The optimal duration of cast immobilization following distal radius fractures (DRFs) in elderly patients has not been established. Objectives.To assess the functional and radiological parameters following DRF treatment in elderly patients using 2 different periods of cast immobilization. Materials and methods.We assessed 50 patients (33 women and 17 men). The mean age at the beginning of treatment was 71 years. The mean duration of follow-up was 1 year and 3 months. One subgroup (n = 26) included p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The meta-analysis of a comparative study of surgical and conservative treatment by Gutiérrez-Espinoza et al [14] proved the fact that extra-articular fractures had good functional outcomes with nonoperative treatment and surgical treatment with volar locking plates in displaced and partial articular or intraarticular fractures had better outcome and early returned to function. The randomized trial by Olech et al [15] to compare functional and radiological criteria in fractures treated in cast at 4 weeks and 6 weeks showed no significant difference by keeping for 6 weeks except an increase in VT angle. The VAS for pain, radial inclination, radial height, and union rate were similar even in patients whose cast was removed at 4 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…The meta-analysis of a comparative study of surgical and conservative treatment by Gutiérrez-Espinoza et al [14] proved the fact that extra-articular fractures had good functional outcomes with nonoperative treatment and surgical treatment with volar locking plates in displaced and partial articular or intraarticular fractures had better outcome and early returned to function. The randomized trial by Olech et al [15] to compare functional and radiological criteria in fractures treated in cast at 4 weeks and 6 weeks showed no significant difference by keeping for 6 weeks except an increase in VT angle. The VAS for pain, radial inclination, radial height, and union rate were similar even in patients whose cast was removed at 4 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…Boersma et al compared the effects of a one-week to four- to five-week plaster cast immobilization, showing a decrease in scores for DASH and PRWE, yet this outcome did not display statistical significance between the two groups [ 10 ]. In a randomized controlled trial (RCT) conducted by Olech et al on elderly patients, a lower mean Mayo wrist Sscore was reported in the four-week group compared to the six-week group; however, this difference was not statistically significant [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…McAuliffe et al’s study showed a mean VAS score after cast removal in favor of the short-period group with a statistically significant result [ 14 ]. Olech et al’s study revealed a lower VAS score in the four-week group compared to the six-week group, but these differences did not reach statistical significance [ 11 ]. However, a study by Christersson et al reported more pain in the short-term group, though this difference was not significant [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…A prospective RCT evaluating the functional results and costs of the above 2 casting positions in patients aged 65 years and older with DRFs found that VFUD is not superior to FC; further cost analyses reveal that overall costs from VFUD are nearly twice those from FC [30]. As to the period of casting time, an RCT compared the functional and radiographic outcomes following treatment of DRFs in a cast for 4 and 6 weeks in the elderly; The Visual Analogue Scale (VAS) pain score, Mayo Wrist Score (MWS), and VAS activity score are similar between the 2 study groups, and there is no significant between-group difference in terms of radial inclination, union rate, radial height, or bone union [31]. In comparison with surgical treatments, cast immobilization (CI) is non-inferior to VLPF after 1 year in patients aged 65 years and older [32].…”
Section: Non-surgical Treatmentmentioning
confidence: 99%